A study on the mobile phone usage pattern and its dependence among medical students of a college in Kerala, India - George, Shiny; Saif, Namitha; Joseph, Biju Baby (International Journal of Research in Medical Sciences, 2017)
Background: Mobile phones have become an essential part of life. It has become an important accessory carried by everybody not only because they make it easy to keep in touch with people but because of the various facilities they offer especially the internet. The charm of mobile phone is more among young generation and the increasing use may result in dependence. Aim was to study the usage pattern and dependence of mobile phones among medical students. Methods: A cross sectional study conducted among 200 medical students and studied the pattern of usage of mobile phones, common problems encountered and its dependence using a questionnaire. Statistical analysis done using chi square test and a p value of <0.05 is taken as significant. Results: In the present study 35% of the students were frequent users that is they used for >30 minutes per day. Female students were talking more to their parents and male students to their friends followed by their lovers. 49 of them never used to attend the call while driving and 58 of them used to stop the vehicle and attend the call. (p=0.002) Mobile phone dependence was also found to be increased which is evident from ringxiety experienced by 68 students (34%) and waking up from sleep to check the mobile for call or message by 62 students(p=0.000). Out of 68 students with ringxiety, 69% were males and 37% were females (p=0.040). 82 participants (41%) commented that life without mobile will be boring and 50 (25%) said that they will feel alone or unsafe (p=0.001). Conclusions: As dependence is increasing with the excessive use of mobile phones, some interventions are required to motivate the youth against it.